The Form of Dispute Settlement in The Border of Sea Region of Asean State Members and Its Implications to Indonesia - Delfiyanti, Delfiyanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2020)
The ASEAN Charter itself has been recently effective on 15th December 2008 after going through the ratification of the ASEAN state members that have ratified a charter that makes the regional bloc into an